Analisis Kriteria Sistem Jaminan Halal pada Produksi Susu di PT. Greenfields Indonesia Tahun 2019 - Hartina, Siti; Syahrir, Achmad; Atmaja, Ria Ramadhani Dwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
World demand for halal pharmaceutical products, which include food, cosmetics, drugs, and other products will continue to grow with the increasing of global Moslems population in the world. Milk is one of the pharmaceutical products produced from livestock commodities. It is processed into 2 types of products namely ESL and UHT milk. In Indonesia, the halal status of a product is a crucial point for consumers who are predominantly by Moslems. In its processing, Indonesian Ulema Council (MUI) has a rule called HAS 23101, a halal certification requirement as an implementation of Halal Guarantee System. This study examines the importance of the Halal Assurance System criteria in milk production in the Indonesian food industry. The purpose of this study is to analyse the suitability of the halal guarantee system criteria for milk production in PT. Greenfields Indonesia based on HAS 23101 standards. This research is a descriptive observational study. The data collection process is carried out by providing a checklist to the halal management team in the food industry. The results obtained are the percentage of conformity to the 100% Halal Policy, 100% Halal Management Team, 100% Training and Education, 100% Material, 100% Product, 91.6% Product Facility, Written Procedure for Critical Activity 100%, 100% Search Capability, Products that do not meet 77.8% criteria, 100% internal audit, and 100% management review. The percentage of conformity results obtained as a whole was 97.2%.